A Visual Analytical Dashboard on Cyber Journalism: An Empirical Review - P SUDHANDRADEVI , Dr.V.BHUVANESWARI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Similar to humans, billions of stars who have made information visible and shareable surround us via digital platforms. Social media is a technology that debuted in 2000, sparking a digital revolution and transforming people's lives. Hundreds of millions of people use the internet to share their ideas, conduct bank transactions, make online purchases, and play online games. Technological innovation harms security and privacy. According to statistics, there were 27,000 crimes perpetrated in 2017, with one every ten minutes on average. A complex and multilayered cybercrime economy, like cybercrime itself, has signalled a fundamental shift. The term "web to profit" has been coined to describe cybercrime. The major aim of this work is to create an analytical dashboard that provides critical summaries of cyber vulnerability data from newspapers between 2012 and 2018. This dashboard provides significant insights into key parameters and allows users to make data-driven decisions on unstructured data. The dashboard displays a variety of insights from the cybercrime dataset, including demographic data, socioeconomic statistics, and quantitative information. The 'Rpubs' online publishing service was used to construct and publish the Cybercrime Analytical Dashboard on the web. The secondary objective of this work is to create an artificial intelligence (AI)-based chatbot that spans the cybercrime and cyber law domains specifically and what it is intended for. A chatbot represents the conversation between the user and an AI assistant. The limitation of the work is that a minimum amount of data has been collected in the dashboard, and it feeds a minimal number of intents to the machine to obtain a response from the chatbot. Future work will integrate this chatbot into the dashboard and not be restricted by crime laws.